On-line measurement of the absolute humidity of air, breath and liquid headspace samples by selected ion flow tube mass spectrometry - Spanĕl, P; Smith, D (Rapid communications in mass spectrometry, 2001)
We describe how selected ion flow tube mass spectrometry (SIFT-MS) can be used to determine the absolute humidity of air, breath and liquid headspace samples. This involves the determination of the relative count rates of the H3O+ ions and those H3O+.(H2O)(1,2,3) hydrate ions that inevitably form in the helium carrier gas when humid samples are being analysed by SIFT-MS using H3O+ precursor ions. This requires an understanding of the kinetics of hydrated hydronium ion formation, the involvement of mass discrimination in the analytical quadrupole mass spectrometer and the decreased diffusive loss of the heavier hydrates along the flow tube. Thus, we show that the humidity of breath and liquid headspace samples, typically at the few percent level, can be directly obtained on-line to the SIFT-MS instrument along with the concentrations of trace gases, which are present at much lower levels. We emphasise the value of parallel humidity measurements in ensuring good real-time sampling of breath and liquid headspace and the value of such measurements to trace gas analysis using SIFT-MS.